Behavioral Intention Analysis on Internet Banking Usage at Bank XYZ Bogor - Fitria Annilda; Ujang Sumarwan; Endar Nugrahani (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
The aims of this paper were to analyze the customer decision to use internet banking and to anlyze the factors correlated with the intention of internet banking usage at XYZ Bank, Bogor, Indonesia. The theoretical foundation for this study was Theory of Planned Behavior (TPB). TPB is a model that estimates the consumers’ intention to perform a behavior or action. A number of 150 respondents were selected by convenience sampling method using questionnaires with interviews. The data were analyzed using SEM-PLS. The results showed that perceived behavior control had a significant influence on behavioral intention. Respondents who had higher scores of perceived behavior were more likely to have a higher intention of using internet banking. For the managerial implications, the company is expected to provide more user-friendly and attractive facilities for users, so that users can easily do banking transactions without having to queue at either a Bank or ATM counters. Second, the facility with more limit than that exists now can be used as a reference for the company to increase the number of internet banking users, so users can use facilities safely, and desired facilities are available in internet banking.Keywords: behaviour intention, internet banking, SEM-PLS, theory of planned behavior